Study on anxiety, depression, and subjective wellbeing of patients with bladder cancer in their different chemotherapy stages - Yang, Jie; Tan, Yingchun; Yao, Chunlin (Frontiers in Psychology, 2023)
The study aims to explore the changes in anxiety, depression, and subjective well-being in patients with bladder perfusion during different stages of their chemotherapy, and analyze the correlation between their anxiety, depression, and subjective well-being.Methods: A total of 174 patients with bladder cancer who received bladder perfusion chemotherapy are selected. The questionnaire survey is conducted with SAS, SDS, and GWB. The patients are surveyed and the data are analyzed.The results of patients' anxiety, depression, and subjective well-being show a dynamic change trend. The change is most obvious after 1 month of chemotherapy and tends to be flat after 3 months of chemotherapy. The scores of anxiety, depression, and subjective well-being in patients with bladder perfusion at different stages are statistically significant (P < 0.05). There is a negative correlation between anxiety, depression, and subjective well-being in patients (r = -0.605, 0.601).Patients' emotions change obviously in the first 3 months of their chemotherapy. Clinical workers can take active intervention measures in this period, guide patients to relieve their anxiety and depression, increase their subjective well-being level, and improve their quality of life, which is helpful to ensure the successful completion of chemotherapy.